Vascular ultrasound, the potential of integration of multiparametric ultrasound into routine clinical practice. (August 2018) - Rafailidis, Vasileios; Sidhu, Paul S
Introduction: Ultrasound has traditionally been regarded as the first-line imaging modality for screening, diagnostic evaluation and monitoring treatment and disease progression of vascular pathology, including both the arterial and the venous branch of the vascular system. Albeit of its well-tolerated nature, wide availability and low cost, ultrasound above all, has the advantage of providing the clinician with clinically significant information related to both intraluminal irregularities and extravascular disease. Ultrasound has the potential not only to anatomically describe tissues but also to assess physiology by evaluating blood flow characteristics in real time. Discussion: The already fundamental role of ultrasound has been even more expanded with the introduction of newer techniques like contrast-enhanced ultrasound, tissue-elastography and 3D ultrasound and the incorporation of research advances into clinical practice. The purpose of this review is to present and discuss some of the latest advances in the field of vascular ultrasound in attempt to illustrate how the adoption of multiparametric ultrasound into everyday clinical practice could address the patient's needs. Pathology and applications discussed include carotid and aortic disease, portal and peripheral venous abnormalities. Conclusion: Widespread availability of modern technology in ultrasound devices has made the application of contrast-enhanced ultrasound, tissue elastography and 3D ultrasound feasible options, ready to contribute to the diagnostic performance of the ultrasonographic technique.